2015
DOI: 10.1523/jneurosci.3611-14.2015
|View full text |Cite
|
Sign up to set email alerts
|

Role of the Indirect Pathway of the Basal Ganglia in Perceptual Decision Making

Abstract: The basal ganglia (BG) play an important role in motor control, reinforcement learning, and perceptual decision making. Modeling and experimental evidence suggest that, in a speed-accuracy tradeoff, the corticostriatal pathway can adaptively adjust a decision threshold (the amount of information needed to make a choice). In this study, we go beyond the focus of previous works on the direct and hyperdirect pathways to examine the contribution of the indirect pathway of the BG system to decision making in a biop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
109
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(116 citation statements)
references
References 104 publications
6
109
0
1
Order By: Relevance
“…Our results are broadly consistent with models suggesting that basal ganglia (BG) nuclei play a role in setting decision thresholds [1926]. However, our patients showed impairments in the ability to combine prior information with sensory information to guide decisions.…”
Section: Discussionsupporting
confidence: 91%
“…Our results are broadly consistent with models suggesting that basal ganglia (BG) nuclei play a role in setting decision thresholds [1926]. However, our patients showed impairments in the ability to combine prior information with sensory information to guide decisions.…”
Section: Discussionsupporting
confidence: 91%
“…This finding highlights the importance of a network perspective on brain activity, whereby the basal ganglia show their role in defining the whole-brain dynamical repertoire. This evidence speaks to a vast literature on the basal ganglia as part of a distributed forebrain network with a prominent role in innate behavioral routines as well as learning (retrieving) new (previously acquired) functional repertoires (64)(65)(66). Previous evidence has shown that extreme specificity is necessary in the connections between the basal ganglia, thalamus and cortex (67)(68)(69), and that the basal ganglia play a prominent role in the fine tuning of such connections (70).…”
Section: Discussionsupporting
confidence: 63%
“…The Cx is the same as described in previous work (Wang, 2002), but with a lower background input to support distributed attractor state. The present model extends an earlier one (Wei et al, 2015) by including the thalamus and replacing the effect of SC in that model by a constant threshold in the Cx. We used the leaky integrate-and-fire model for all the neurons.…”
Section: Methodsmentioning
confidence: 57%
“…Interruption of the disinhibition mechanism of the BG lied in the core of our model for inhibitory control, and has been supported by recent experiments (Schmidt et al, 2013). The indirect pathway of the BG has important roles in proactive inhibitory control (Majid et al, 2013) and perceptual decision making (Wei et al, 2015). Here we showed that modulation of the relative weights of the BG pathways could effectively modulate the SSRT, which provides a possible source for individual difference of the SSRT.…”
Section: Discussionmentioning
confidence: 99%